(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
In my study I analyse some pieces of József Koszta’s paintings, which depict peasant girls. My goal is to analyse the idea of the child in a rural society in archaic circumstances; I strive to create parallels between the ethnography and the history of childhood concepts. I try to make my study more sophisticated by using the methods of iconography and iconology (Erwin Panofsky). I consider the aspects of content-description, composition analysis, pedagogical antropology and the history of the idea of the child in order to make conclusions with regard to the idea of the child. Koszta was a master of creating melancolical atmosphere and he expressed his own world by his paintings (he was a representative of expressive realism). His paintings depict hard rural life and the lifestyle of peasants at that time, therefore his paintings don’t show the joyful moments of childhood, but the aspects and motives of quiet children and resigned women.